Daring to Dare: Edinburgh International Festivals Diary 2022. Issue 1 (February 2023) - Relich, Mario
Abstract : Mario Relich provides an annual fixture in Scottish Affairs : a personal review of the Edinburgh International Festivals. Themes for 2022 included freedom of speech and the war on Ukraine.